Športna dejavnost študentk in študentov Filozofske fakultete v času epidemije - Jerman Šenica, Metka (Šport (Ljubljana), 2021)
At the end of October 2020, Slovenia was hit by the second wave of SARS-CoV-2 infection, and we only had to interrupt the well-started academic year 2020/2021. Students of the Faculty of Arts of the University of Ljubljana returned to their hometowns and began distance learning. To continue our studies, we downloaded lectures and sports practice online and continued in online classrooms, where participants in sports programs within the subject Sports and Humanities received instructions for sports training and materials. Given that the communication was only via e-mail, I tried to find out with a questionnaire how they cope with this way of fulfilling the obligations in the sports programs I teach and how active they are in sports during the epidemic. Given that they had to report their weekly sports activities, the answers in the questionnaire confirmed my assumption about their exercise at least once a week, and almost a quarter of all also exercise four to five times a week. At the same time, two - thirds of the respondents regularly monitor their sports activity with tracking applications or a sports watch, while the rest have problems with this due to unsuitable telephones or because they do not agree with this way of performing sports activities.
Keywords: epidemic; epidemije; Faculty of Arts; Filozofska fakulteta; sledenje; sports activity; sports practice; športna aktivnost; športna vadba; tracking